Registro de un nuevo afido introducido en Chile: Takecallis taiwanus (Takahashi)(Hemiptera: Aphididae: Drepanosiphinae) - Fuentes Contreras, E.=700 1 Niemeyer, H.M.
(Es, En)
Ilus., 7 ref.
Keywords: HEMIPTERA; APHIDIDAE; TAXONOMIA; REGISTRO; ESPECIES NUEVAS; CHILE; TAKECALLIS TAIWANUS; REVISTA CHILENA DE ENTOMOLOGIA